2010
DOI: 10.1352/1944-7558-115.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Responsivity Predicts Language Development in Young Children With Fragile X Syndrome

Abstract: The relationship between early maternal responsivity and later child communication outcomes in young children with fragile X syndrome was investigated. Data were obtained from 55 mother–child dyads over a 36-month period. Performance data were obtained at each measurement point from video observations of four different contexts. These were coded for (a) child communication behaviors, (b) parent responsivity, and (c) behavior management behaviors. Results indicate that early maternal responsivity predicts the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
168
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(188 citation statements)
references
References 55 publications
13
168
2
5
Order By: Relevance
“…The prevalence of autism in FXS is estimated between 25% and 50% (see McDuffie et al, 2010), and is often an indicator of greater delays in communication and language (Abbeduto et al, 2007;Lewis et al, 2006;Philofsky, Hepburn, Hayes, Hagerman, & Rogers, 2004;Roberts, Mirrett, & Burchinal, 2001;Warren, Brady, Sterling, Fleming, & Marquis, 2010). However, several studies have reported no distinct language profiles between individuals with comorbid FXS and autism and individuals with FXS only, particularly in areas of expressive language, such as morphosyntax (Estigarribia et al, 2011;Lewis et al, 2006;Price et al, 2008), lexical diversity, talkativeness, and dysfluency .…”
Section: Factors Related To Language Development In Fxsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of autism in FXS is estimated between 25% and 50% (see McDuffie et al, 2010), and is often an indicator of greater delays in communication and language (Abbeduto et al, 2007;Lewis et al, 2006;Philofsky, Hepburn, Hayes, Hagerman, & Rogers, 2004;Roberts, Mirrett, & Burchinal, 2001;Warren, Brady, Sterling, Fleming, & Marquis, 2010). However, several studies have reported no distinct language profiles between individuals with comorbid FXS and autism and individuals with FXS only, particularly in areas of expressive language, such as morphosyntax (Estigarribia et al, 2011;Lewis et al, 2006;Price et al, 2008), lexical diversity, talkativeness, and dysfluency .…”
Section: Factors Related To Language Development In Fxsmentioning
confidence: 99%
“…(Warren et al, 2010, p. 54). Two previous studies of children with FXS defined and measured responsivity according to the types of facilitative input and responses provided by mothers (Brady, Warren, Fleming, Keller, & Sterling, 2014;Warren et al, 2010). These studies specifically looked at how responsivity affected vocabulary outcomes.…”
Section: Factors Related To Language Development In Fxsmentioning
confidence: 99%
“…The second main finding of the previous research is that children's rates of cognitive and communication development are positively correlated with their mother's level of responsiveness (e.g., Kim & Mahoney, 2005;Mahoney & Nam, 2011;Mahoney & Perales, 2003;Mahoney, Perales, Wiggers, & Herman, 2006;Yoder & Warren, 1998;Warren, Brady, Sterling, Fleming, & Marquis, 2010).These findings have not only been reported in descriptive research studies but also shown in experimental intervention studies (e.g., Kim & Mahoney, 2005;Yoder &Warren, 1998) as well. This effect has been reported with children who have diverse etiologies such as DS or autism as well as with children who have different IQs or DQs.…”
mentioning
confidence: 78%
“…Studies that are focused on parent-child interaction (e.g., Karaaslan, Diken, & Mahoney, 2011;Mahoney, Boyce, Fewell, Spiker, & Wheeden, 1998;Mahoney, Powell, & Finger, 1985) also indicated that parents' interactional behaviors that are highly directive and relatively nonresponsive do not support an increase in the development of their child with disabilities (cited in Diken, 2012).Furthermore, a qualified parent-child interaction seems to decrease the disability of children with developmental delay, including DS and autism. It has been clearly established in the literature (e.g., Mahoney & Nam, 2011;Mahoney & Perales, 2003;Mahoney et al, 2006;Tamis-LeMonda et al, 2001;Tamis-LeMonda, Shannon, Cabrera, & Lamb, 2004;Warren et al, 2010) that during the early childhood years, parents promote the development of their children who have disabilities, including DS and ASD, by engaging in highly responsive interactions throughout their daily routines. Consistent with this interpretation, findings reported by the existing literature on parentchild interactions (e.g., Brady, Warren, & Sterling, 2009) revealed that responsiveness is also a primary influence on a child's development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation